Comparing dexmedetomidine and propofol for sedation and hemodynamic stability in cardio-thoracic intensive care unit for patients following off-pump coronary artery bypass graft surgery - Patil, Vasant P.; Abraham, Jacob; George, Grace M. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Most patients in intensive care unit (ICU) require both sedation and analgesia to encourage natural sleep, facilitate assisted ventilation and modulate physiologic response to stress. The ideal sedative after Coronary artery bypass grafting (CABG) should have rapid onset, immediate resolution of both pain and anxiety, promote cardiac and respiratory stability, maintain a reusability during sedation, allow rapid recovery after discontinuation, and attenuate the cardiovascular, neuroendocrine, and inflammatory response. All these properties may improve outcome in cardiac patients after CABG. Methods: Setting-cardiac ICU. A prospective, randomised, single blind study including 60 patients divided into 2 groups. Data collection tools-study proforma and Ramsay sedation scale (RSS). Data analysed using science and statistical packaged (SPSS) version 20, independent sample `t` test, chi-square test, analysis of variance (ANOVA) and p value ≤0.05 was considered statistically significant. Results: Sedation levels and length of stay of patients on ventilator were comparable in both groups, however, analgesic requirement was significantly less in dexmedetomidine group. Dexmedetomidine group showed significantly lower heart rates compared to propofol group. Conclusions: Dexmedetomidine and propofol are safe sedative agents during mechanical ventilation in ICU for patients undergoing off pump coronary artery bypass (OPCAB). There is more than 50% reduction in analgesic requirement and a significant reduction in heart rate in dexmedetomidine sedated patients.